The Lake Albert Rift (Uganda, East AfricanRift System): sediment budget, deformation,basin and relief evolution since 17 Ma - (:unkn) unknown (My University, 2016)
This study is based on a coupled basin infilling study and alandforms analysis of the Lake Albert Rift located at the northernpart of the western branch of the East African Rift.The basin infilling study is based on both subsurface data andoutcrops analysis. The objective was to (1) actualize age model,(2) to reconstruct the 3D architecture of the rift using sequencestratigraphy correlations and seismic data interpretation, (3) tocharacterize the deformation and its changes through times and(4) to quantify the accommodation for several time intervals. Theinfilling essentially consists of isopach fault-bounded units composedof lacustrine deposits wherein were characterized two majorunconformities dated at 6.2 Ma (Uppermost Miocene) and2.7 Ma (Pliocene-Pleistocene boundary), coeval with major subsidenceand climatic changes.The landforms analysis is based on the characterization and relativedating of Ugandan landforms which consist of stepped planationsurfaces and incised valleys. We here proposed a seven-stepsreconstruction of the deformation-erosion-sedimentation relationshipsof the Lake Albert Basin and its catchments:- 55-45 Ma: formation of laterites corresponding to the AfricanSurface during the very humid period of the Lower-Middle Eocene;- 45-22: stripping of the African Surface in response of the beginningof the East-African Dome uplift and formation of a pediplainwhich associated base level is the Atlantic Ocean;- 17-2.5 Ma: Initiation of the Lake Albert Basin around 17 Ma andcreation of local base levels (Lake Albert, Edward and George) onwhich three pediplains tend to adapt;- 18-16 Ma to 6.2 Ma: ”Flexural” stage (subsidence rate: 150-200 m/Ma; sedimentation rate 1.3 km3/Ma between 17 and 12Ma and 0.6 km3/Ma from 12 to 6 Ma) – depocenters location(southern part of Lake Albert Basin) poorly controlled by fault;- 6.2 Ma to 2.5 Ma: Rift stage 1 (subsidence rate: > 500m/Maup to 600-800 m/Ma; sedimentation rate: 2.4 km3/Ma) – Riftingc
Keywords: African Research